Lysophosphatidylcholine Alleviates Acute Lung Injury by Regulating Neutrophil Motility and Neutrophil Extracellular Trap Formation - Jeong, Soi; Kim, Bora; Byun, Da Jeong; Jin, Sunmin; Seo, Bo Seung; Shin, Mi Hwa; Leem, Ah Young; Choung, Jai Jun; Park, Moo Suk; Hyun, Young-Min (Frontiers in Cell and Developmental Biology, 2022)
Sepsis is predominantly initiated by bacterial infection and can cause systemic inflammation, which frequently leads to rapid death of the patient. However, this acute systemic inflammatory response requires further investigation from the perspectives of clinical judgment criteria and early treatment strategies for the relief of symptoms. Lysophosphatidylcholine (LPC) 18:0 may relieve septic symptoms, but the relevant mechanism is not clearly understood. Therefore, we aimed to assess the effectiveness of LPC as a therapeutic treatment for acute inflammation in the lung induced by lipopolysaccharide in mice. Systemic inflammation of mice was induced by lipopolysaccharide (LPS) inoculation to investigate the role of LPC in the migration and the immune response of neutrophils during acute lung injury. By employing two-photon intravital imaging of the LPS-stimulated LysM-GFP mice and other in vitro and in vivo assays, we examined whether LPC alleviates the inflammatory effect of sepsis. We also tested the effect of LPC to human neutrophils from healthy control and sepsis patients. Our data showed that LPC treatment reduced the infiltration of innate immune cells into the lung. Specifically, LPC altered neutrophil migratory patterns and enhanced phagocytic efficacy in the damaged lung. Moreover, LPC treatment reduced the release of neutrophil extracellular trap (NET), which can damage tissue in the inflamed organ and exacerbate disease. It also reduced human neutrophil migration under inflammatory environment. Our results suggest that LPC can alleviate sepsis-induced lung inflammation by regulating the function of neutrophils. These findings provide evidence for the beneficial application of LPC treatment as a potential therapeutic strategy for sepsis.